The Prevalence of Spinal Abnormalities in Students with Visual and Hearing Impairment - Mojgan Farahbod; Mina Ahmadi-Kahjoogh; Hossein Ahmadi-Kahjoogh (Vesnu Publications, 2015)
Introduction: Vertebral Colum is the main axis of the body that has an important role in keeping a proper posture. The aim of this study is to investigate the prevalence of vertebral deformities in children with impaired sight and hearing. Materials and Methods: Ten percent of students in elementary and preschool and students in the academic year of 2012-2013 were selected for this study. In Tehran, Iran 323 people, 244 people in the cities of the Tehran Province and in Alborz, Iran Province 148 students. Demographic questionnaire, Taiwanese flexible ruler, plummet and a simple rule were used for data collection. Data was reported using descriptive statistics. Results: The results indicated that, male and female students with visual impairment in Alborz province, Iran had the highest prevalence. In the first and third quartiles kyphosis, students with hearing impairment in Alborz province were in a worse situation. In the first quarter of lordosis, girls with hearing impairment in Tehran had the highest degree and in the third quarter, the boys with visual impairments of Alborz province had the same condition. Conclusion: Based on the findings, it can be concluded that students of Alborz province are suffering more than other students with similar disorders in Tehran and cities of the Tehran from abnormalities of the spine. Therefore, in theses students it is necessary to provide training and rehabilitation services for correcting abnormalities or appropriate use of alternative senses in the body.